The Correlation Of The Emotional Bonding Between The Stunting Children Under Five Years In The Slum Area Of Makassar City, South Sulawesi, Indonesia - Hasriwiani Habo Abbas; Andi Multazam; Sri Utami Megantari; Husnul Khatimah; Sarah Sarah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Stunting is a linear growth and development disorder caused by malnutrition in nutrient intake, chronic infectious diseases, and inadequate psychosocial stimulation. Children are defined as stunted if their height-for-age is more than two standard deviations below the WHO Child Growth Standards median. According to the World Health Organization categorized of stunting cases if the prevalence rate of stunting 30-39 % was high cases, and if the cases of stunting ≥ 40% were categorized as extremely high stunting cases. Based on data from the Ministry of Health The prevalence of stunting under five in Indonesia in 2005-2017 in Indonesia is 36.4%. The survey of Monitoring Nutritional Status of South Sulawesi has been conducted in 24 districts/cities it shows that the prevalence of stunting under five in 2014 was 34.5%. Decreased in 2015 to 34.1%. Then an increase in 2017 reached 34.8%. This figure shows that the position of South Sulawesi in 2017 has not yet reached the SDGs target. According to UNICEF (2013), the cause stunting factors are caused by various factors, family and household factors (mother factors, home environment), inadequate breastfeeding, breastfeeding, and infection. Contextual factors that contribute to the incidence of stunting are political economy, health services, education, socio-culture, agricultural and food systems, and water sanitation environments. To an analysis of correlation the emotional bonding and attachment factors to the stunting of children under five years in the slum area of Makassar City, South Sulawesi, Indonesia. The analysis correlation between parenting pattern (quality time and eating pattern), history of breastfeeding, weaning age to emotional bonding and attachment, and the analysis correlation between the emotional bonding and attachment with the stunting. The design of analysis is a cross-sectional analytic design. The sample of this study is 150 Children under five years. The analysis correlation between parenting pattern (quality time and eating pattern), history of breastfeeding, weaning age that shows a significant correlated to the emotional bonding and attachment, the p-value: (0.027&0.000), 0.000, 0.000 < 0.005, respectively. However, the analysis of emotional bonding and attachment to the stunting is a significant correlation, the p < value, 0.000< 0.005. Attachment is an emotional bond that is formed by an individual with other people that is specific and binds in an eternal closeness over time. Adequate interaction between mother and child can lead to closeness and a sense of security for the child to increase growth and development for the particularly in the first 1000 days from conception until the age of two.